2010
DOI: 10.2214/ajr.09.2326
|View full text |Cite
|
Sign up to set email alerts
|

Radial Scars Without Atypia Diagnosed at Imaging-Guided Needle Biopsy: How Often Is Associated Malignancy Found at Subsequent Surgical Excision, and Do Mammography and Sonography Predict Which Lesions Are Malignant?

Abstract: A percutaneous diagnosis of a radial scar does not exclude associated malignancy at surgical excision. Mammographic and sonographic features of a lesion diagnosed as a radial scar at percutaneous imaging-guided biopsy do not predict which lesions will have associated malignancy at surgery. Therefore, all patients with percutaneous diagnosis of a radial scar should undergo surgical excision regardless of mammographic and sonographic appearances, until further criteria can be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
2
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 24 publications
2
36
2
4
Order By: Relevance
“…With VABB, the rate of underestimates decreases. Linda et al reported a rate of 5% underestimates in 19 cases of RSL proven by 11 G VABB [42]. Tennant et al [48] and Resetkova et al [49] reported no underestimates among 18 or 80 lesions diagnosed as RSL at 11 G VABB, respectively.…”
Section: Lobular Neoplasiamentioning
confidence: 99%
See 1 more Smart Citation
“…With VABB, the rate of underestimates decreases. Linda et al reported a rate of 5% underestimates in 19 cases of RSL proven by 11 G VABB [42]. Tennant et al [48] and Resetkova et al [49] reported no underestimates among 18 or 80 lesions diagnosed as RSL at 11 G VABB, respectively.…”
Section: Lobular Neoplasiamentioning
confidence: 99%
“…The diagnosis of an RSL by CNB is associated with a rate of 9-17% underestimates of DCIS or invasive breast cancer [10,22,42]. With VABB, the rate of underestimates decreases.…”
Section: Lobular Neoplasiamentioning
confidence: 99%
“…Radyal skar 1 cm ve altındaki lezyonlarda, kompleks sklerozan lezyon ise 1 cm'den büyük lezyonlar için kullanılır. Bu lezyonlar aslında benigndir, ancak ADH, DKİS, LKİS ya da invaziv karsinomla beraber olabileceği için artmış risk göstergesi kabul edilir [54].…”
Section: Radyal Skar (Radyal Sklerozan Lezyon)unclassified
“…Kalın iğne biyopsisi ile radyal skar tanısı alan olgularda cerrahi biyopsi ile malignite saptanma oranları da çok değişkendir. Bir grup araştırıcı kalın iğne tanı-sından sonra cerrahi biyopsinin gereksiz olduğunu, radyolojik kontrollerin yeterli olacağını bildirirken, bazı araştırmacılar ise yanlış negatif sonuçlar nedeniyle cerrahi biyopsi yapılma-sını önermektedirler [54][55][56][57][58].…”
Section: Radyal Skar (Radyal Sklerozan Lezyon)unclassified
“…Recently, Rajan et al [46] showed confirmation of radial scars without atypia in 11/14 patients undergoing VAB after an initial diagnosis of non-atypical radial scar. The question whether or not VAB can be recommended as a treatment option in small radial scars without atypia is still under discussion [47].…”
Section: Biopsy As a Therapeutic Option?mentioning
confidence: 99%